Synthesis and Thermal Electo Conductivity of Some New Triazole Derivatives Bearing Azo or Azomethain Group - Saad, Hala Abdel Rahim; Shakir, Raied Mustafa; Mahdi, Mohammad Hady (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Newly acid hydrazide was synthesized from ethyl 2-(2,3-dimethoxyphenoxy) acetate (2), which is cyclized to the corresponding 4-amino-1,2,4-triazole (3). Five newly azo derivatives (4a-e) were synthesized from this 1,2,4-triazole by converting the amine group to diazonium salt then reacted with various substituent phenol,as well three newly imine derivatives (5a-c) were synthesized from reacting the amine group of compound (3) with three aryl aldehyde. The thermal electro conductivity of these compounds was tested at 30, 50, 75 and 100 áµ’C. compound 4a showed interesting electro conductivity at 75áµ’C as well 5a at 75áµ’C while 5b showed significant conductivity at 100 áµ’C